Analisa Faktor-Faktor Penyebab Kecelakaan Lalulintas di Tol Semarang-Solo - Afif Amir Amrullah (Lembaga Pengembangan Kinerja Dosen, 2025)
Between June and early August, six accidents occurred on the Semarang-Solo toll road compared to other toll roads, one of which involved 15 vehicles. To reduce accidents, information on the causes of accidents and the risk factors involved needs to be studied. This research method uses descriptive observational. Data were collected through observations twice during the day and once at night. The results of the study found a relationship between environmental factors, driver factors, and vehicle factors that contribute to the risk of accidents. Suggestions: Efforts are needed to minimize contributing risk factors in order to reduce the risk of accidents. The method used in this study is descriptive observational, with data collected through direct observation at two times during the day and once at night. This approach allows for observation of road conditions and driver behavior at various times, both during the day and night, which often have different levels of accident risk. These observations not only look at the physical condition of the road, but also pay attention to the factors of the drivers and vehicles involved. The results show a significant relationship between environmental factors, driver factors, and vehicle factors that can increase the risk of accidents. Several environmental factors, such as weather conditions, street lighting, and inadequate toll road design, have been found to influence accident rates. Furthermore, driver factors such as fatigue, excessive speed, and negligence also contribute significantly to accidents. Equally important, poorly maintained vehicles or vehicles that do not meet safety standards also play a role in causing accidents. It is recommended that efforts to minimize these risk factors be coordinated between authorities and the public. Improving the quality of toll road infrastructure, providing adequate lighting, and monitoring driver behavior are essential.